Assessment of project management maturity in EPC company using project management maturity model (PMMM) framework - Candrikha Revikesya; Ayudita Oktafiani; Intan Permatasari (Universitas Sultan Ageng Tirtayasa, 2026)
Project performance, particularly in terms of schedule efficiency, remains a critical issue in Engineering, Procurement, and Construction (EPC) projects due to its inherent complexity. Previous studies have highlighted that insufficient project management capability is a key factor contributing to project delays and inefficiencies. However, empirical studies examining project management maturity in EPC organizations remain limited. This study aims to assess the project management maturity level of an EPC organization using the Project Management Maturity Model (PMMM). A quantitative approach was employed using a structured self – assessment questionnaire covering ten project management knowledge areas. The data were analyzed using ordinal measurement, where the maturity level was determined based on the lowest maturity score across all knowledge areas. The results indicate that the organization is at Level 2 of maturity, with variations across knowledge areas ranging from Level 2 to Level 4. Critical areas, project resource management, were identified as having lower maturity levels. These findings suggest that although basic project management processes already exist, their implementation remains inconsistent and not yet standardized across the organization. The study also highlights the importance of advancing toward higher maturity levels to improve consistency, coordination, and project performance. The findings contribute to the understanding of project management maturity in EPC environments and provide practical insights for organizations to enhance their project management capability.